The Role of Entrepreneurial Orientation and Entrepreneurial Leadership of SMEs in the City of Surakarta, Indonesia - Harjono Harjono; Boge Triatmanto; Bambang Supriadi (Innovation Business Management and Accounting Journal, 2024)
This research analyzes entrepreneurial leadership and orientation's influence on business performance with competence as a mediating variable in Bakery SMEs in Surakarta City. The design of this research is explanatory causality research with a quantitative approach. The number of samples is determined using Slovin and simple random sampling of 189 respondents. The analytical tool used was SPSS description analysis. The study results showed entrepreneurial orientation, leadership, competence, and business performance perceptions. Entrepreneurial orientation in SMEs in Surakarta is empirically reflected by the courage to take risks, innovativeness, economy, and reactivity. The indicator of daring to take risks has the highest contribution value, especially regarding the courageous attitude of business actors to accept risks from the business they are running. Entrepreneurial Leadership in SMEs in Surakarta is empirically reflected by being brave enough to act, sociable, broad-minded, big-hearted, and self-confident. The self-confidence indicator has the highest contribution value, especially regarding the ability of bread SMEs in Surakarta to run a business that never gives up from the various obstacles they face. Knowledge, skills, self-concept, character, and motives empirically reflect competence.